Analysis on VANET routing protocols - Zhen-hua WU; Peng HU (Tongxin xuebao)
Many present VANET routing algorithms were carefully analyzed and the result turned to classify into 4 classes:location based greedy routing algorithm,anchor node based routing algorithm,street row based routing algorithm and cluster based routing algorithm.Characters for each kind of algorithm were implemented and compared to each other by using the NS2.The experiment data and analysis result will provide a new subject for further research of VANET routing.